2016
DOI: 10.3390/met6010022
|View full text |Cite
|
Sign up to set email alerts
|

Deformation in Metallic Glasses Studied by Synchrotron X-Ray Diffraction

Abstract: Abstract:High mechanical strength is one of the superior properties of metallic glasses which render them promising as a structural material. However, understanding the process of mechanical deformation in strongly disordered matter, such as metallic glass, is exceedingly difficult because even an effort to describe the structure qualitatively is hampered by the absence of crystalline periodicity. In spite of such challenges, we demonstrate that high-energy synchrotron X-ray diffraction measurement under stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In single-crystal nanowires, the high surface mobility of the constituent elements induced large anelasticity 27 . It was also found that elastostatic loading and creep experiments induced structural anisotropy in metallic glasses [28][29][30] . In the case of cryothermal cycling, plunging of the sample into a vessel of liquid nitrogen creates an immediate temperature gradient, which creates biaxial tension in the surface plane, initiating anelastic local flow.…”
Section: Resultsmentioning
confidence: 98%
“…In single-crystal nanowires, the high surface mobility of the constituent elements induced large anelasticity 27 . It was also found that elastostatic loading and creep experiments induced structural anisotropy in metallic glasses [28][29][30] . In the case of cryothermal cycling, plunging of the sample into a vessel of liquid nitrogen creates an immediate temperature gradient, which creates biaxial tension in the surface plane, initiating anelastic local flow.…”
Section: Resultsmentioning
confidence: 98%
“…As Bragg diffraction is a discrete Fourier series of an infinite periodic structure, the discrete points Q i forming the reciprocal lattice, and coefficients expressed by structure factors S i , amorphous disordered systems have to be treated in a continuous Fourier integral with a continuous scattering function S(Q). The back-transformation from an amorphous diffraction pattern leads to the pair distribution function or radial distribution function, as briefly introduced by Egami et al [14]. Similarly, electrons scatter from atoms and form diffraction patterns, which can be obtained by measuring the extended X-ray absorption fine structure, known as EXAFS.…”
Section: Metallic Glass and Disordered Crystalsmentioning
confidence: 99%
“…Likewise, Egami et al [14] treat the atomic response of metallic glass to perturbations by a uniaxial mechanical load, breaking the symmetry of the system and extracting further information on the amorphous microstructure over length-scales. Non-affine atomic rearrangements below the yield stress have been found to be localized and reversible, leading to the abovementioned pseudo-elasticity.…”
Section: Metallic Glass and Disordered Crystalsmentioning
confidence: 99%
“…The use of in situ characterization techniques is, however, still limited to diffraction of synchrotron radiation [11][12][13]. Recently, more sophisticated techniques of real-time in situ synchrotron X-ray tomographic microscopy [14] and combination of time-resolved X-ray photon correlation spectroscopy and high-energy XRD [15] were applied.…”
Section: Metallic Glasses and Nanocrystalline Alloysmentioning
confidence: 99%